The Impact Of AI ChatGPT On The Challenges and Opportunities for Civics Teachers In The Gen Z Era - sugiyo, ragil andriansyah; Effendi, Yulius Rustan; Iswahyudi, Didik (Universitas Putra Indonesia YPTK Padang, 2025)
This study examines how character-based ChatGPT, a form of artificial intelligence, affects challenges and opportunities for Pancasila and Civic Education (PPKn) teachers. It looks at how teachers instill Pancasila values in Generation Z students at Taman Harapan High School. The research uses a qualitative, case study approach. Data was collected through in-depth interviews with PPKn teachers, ICT teachers, the vice principal overseeing curriculum, and students in grades IX–XII. Findings were enriched by classroom observations and analysis of teaching modules and attendance records. Character-based AI can enrich learning by sparking critical discussion, expanding resource access, personalizing reinforcement, and increasing motivation. Risks include academic ethics, reduced contextual meaning, unequal access to devices and connectivity, and educators' readiness. Teachers must improve their digital literacy, content curation, and assessment strategies to use AI for strengthening, not replacing, character-building. The study recommends tiered training in ethical AI use, clear school technology policies, monitoring mechanisms for student AI use, and providing basic infrastructure.The contribution of this research lies in the formulation of a character-based digital pedagogy framework that is in line with the principles of Pancasila, while also providing a practical basis for schools in designing inclusive, safe, adaptive, and meaningful 21st-century learning interventions. The findings also emphasize the need for teacher-parent collaboration to guide the productive use of AI, the development of digital classroom SOPs, and the development of originality assessment rubrics. Going forward, further research is recommended to explore cross-subject integration models and test the effectiveness of interventions through classroom action research designs in the Indonesian context